Estimation Method of the Consolidation Potential of Rural Residential Land considering Farmers’ Willingness - Bo Liu; Chen Chen; Liang Tang; Zhisong Chen; Cheng Cao (Discrete Dynamics in Nature and Society)
The work of rural residential land consolidation is related to several aspects, such as optimization of the structure of rural layout and improvement of the ecological environment in rural areas. Therefore, the work of rural residential land consolidation must be carried out rationally and effectively on the basis of scientific estimation of the real potential of rural residential land consolidation. However, according to the existing estimation method of the consolidation potential of rural residential land, it ignores the willingness of farmers who are closely related to it and cannot meet the current requirements of rural residential consolidation. Under the background of rural revitalization and based on the new requirements of standardizing rural land improvement work, this study organically combines rural residential land consolidation and the protection of farmers’ land rights and interest from the perspective of farmers’ wishes. The research uses a multimethod integrated approach (the per-capita construction land standard method, per-household construction land standard method, and town system planning method) to measure theoretical potential of the rural residential land consolidation and constructs a correction index system in two dimensions: natural conditions and economic feasibility. And then, this study further optimizes the correction index system from the perspective of farmers’ willingness. Finally, the feasibility of the estimation method is verified by a case. The research will initiate new ideas for estimating land consolidation potential in residential areas and provide references for the work and the special plan of rural residential land consolidation in various localities.